2014
DOI: 10.1038/nchembio.1475
|View full text |Cite
|
Sign up to set email alerts
|

G quadruplexes are genomewide targets of transcriptional helicases XPB and XPD

Abstract: G4 motifs are greatly enriched near promoters, suggesting that quadruplex structures may be targets of transcriptional regulation. Here we show, by ChIP-Seq analysis of human cells, that 40% of the binding sites of the transcription-associated helicases, XPB and XPD, overlap with G4 motifs. The highly significant overlap of XPB and XPD binding sites with G4 motifs cannot be explained by GC-richness or parameters of the genomewide analysis, but instead suggests that these proteins are recruited to quadruplex st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
185
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(194 citation statements)
references
References 60 publications
8
185
1
Order By: Relevance
“…The fact that many cells can readily take up G4DNA indicates that this mechanism may also allow the cell to respond to its external environment as well as internal stress (67,72). Although our results suggest important roles for G4DNA in the regulation of cytoplasmic cellular processes, other studies have suggested roles for G4DNA in modulating transcription through the binding of helicases such as DHX36 (30,96,97), the RecQ family helicases (98,99), and the XPB and XPD helicases (75). It is possible that any G4DNA-binding protein may be regulated by freely diffusing G4DNA, leading to various cellular responses based on the large number of proteins that are reported to have G4DNA binding capacity (4, 100 -102).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The fact that many cells can readily take up G4DNA indicates that this mechanism may also allow the cell to respond to its external environment as well as internal stress (67,72). Although our results suggest important roles for G4DNA in the regulation of cytoplasmic cellular processes, other studies have suggested roles for G4DNA in modulating transcription through the binding of helicases such as DHX36 (30,96,97), the RecQ family helicases (98,99), and the XPB and XPD helicases (75). It is possible that any G4DNA-binding protein may be regulated by freely diffusing G4DNA, leading to various cellular responses based on the large number of proteins that are reported to have G4DNA binding capacity (4, 100 -102).…”
Section: Discussioncontrasting
confidence: 47%
“…2I) were also found in stress granules induced by G4DNA. The fraction of stress granule protein foci that contain G4DNA foci was determined to be 90,7,75,96,17, and 83% of the TIA1, DHX36, YB-1, ELAV1, G3BP, and eIF3 foci, respectively. The fraction of DHX36 and G3BP foci containing G4DNA was significantly lower than the other stress granule proteins.…”
Section: Resultsmentioning
confidence: 99%
“…These facts suggest G-quadruplex structures have implications in physiological processes. Indeed, experimental investigations have demonstrated the physiological function of G-quadruplexes in many aspects (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…G4 DNA can be bound and unwound by RECQ helicases (10), and by the XPD-related helicases such as human XPD (19) and its paralogs FANCJ (20,21), CHL1 (22), and likely RTEL1 (23). In the human genome, G4 motifs are greatly enriched near transcription start sites (TSS), at the 5â€Č end of first introns, and in exons and introns of many oncogenes (reviewed in refs.…”
mentioning
confidence: 99%